Design and Development of Android based Multimedia Player (International Journal of Innovative Research in Computer Science & Technology, 2020)
In today`s world, many users like to use  media player in order to solve the complex functions and large  memory requirement in a smart phone. With a rapid growth of  network and technology, multimedia technology is used in  media players. As the Android based devices are getting more  popular among the people, an Android based application  attracts more attention. Based on Android technology and  java language the design and coding of a simple, convenient,  less memory requirement as well as user friendly multimedia  player is shown in this paper. The player is designed in such a  way to obtain higher performance; simple operations and run  on the Android based mobile devices. The papers discuss  about the study of multimedia player with the help of already  existing media players which are available openly in the  Android market and proposed system for multimedia player  that will be providing the uninterrupted enjoyment for the  users.
Keywords: Android; Multimedia; Smartphone; Media player; Audio player